Barbare Jorjadze’s work in the context of feminist criticism - Chumburidze, Sofiko (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2021)
From the second half of the nineteenth century, like in Europe and America, the issue of women’s emancipation began to be actively debated in Georgia. It is noteworthy that during this period women themselves began to fight for their rights, and the turning points in the spiritual realm were reflected in their work in an interesting way; the difficulties and internal contradictions that accompanied the liberation from traditional morality became apparent. Female authors were well aware of the new realities and social challenges that emancipated women faced. Barbare Jorjadze (1833-1895), an excellent representative of Georgian culture of the nineteenth century, a writer, and public figure, was one of the first fighters for the emancipation of women. Advancing the fight for women’s rights also highlighted the problem of the relationship between literature and feminism. Consequently, a feminist critique of literature also emerged. Feminist critique is interested in the female author and not the female reader. Were the women authors educated? What are the peculiarities of their autobiographical texts? Did they need to use pseudonyms? How was their work perceived and valued in a given society? Male authors mostly wrote about women as mothers and were less interested in their legal status. By the end of the nineteenth and early twentieth centuries, women were already realizing that they had to create their own lives. Women were seen as a group oppressed by men, invoking examples and history from the past to reinforce their arguments and discuss women’s condition, and their problems globally. This article discusses Barbare Jorjadze›s work in the context of feminist critique. Georgian feminist critique of the second half of the nineteenth century would have been inconceivable without the letters of Barbare Jorjadze about the problems of women and their social status. She focused on an unacceptable tradition, the change of which was the main task. Barbare Jorjadze›s work was an example for Georgian women to defend their rights and take an active part in the public arena. This „home-grown woman“, as she was ridiculed by her opponents, portrays the situation of women in Georgia quite well. Barbare Jorjadze’s work and her past life proved that she had never gotten used to the difficult situationfor a woman. She was able to become a notable person of her time through her tireless work and struggle, and her work clearly shows the necessity of the struggle for gender equality and the urgent need in the Georgian life of the second half of the XIX century.